2018
DOI: 10.1177/1078155218804042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the adverse effects of melphalan formulations

Abstract: Introduction For multiple myeloma patients who respond to primary therapy, autologous hematopoietic stem cell transplant (HSCT) is considered standard of care with high-dose melphalan for transplant candidates. There are now two different melphalan formulations available, including a propylene glycol containing (PG-MEL) product and a propylene glycol-free (PG-free MEL) product. Although considered bioequivalent, there remains limited literature directly evaluating the adverse events between the two agents. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[16][17][18] One study found PG melphalan to have a higher rate of mucositis and a separate study found PG-free melphalan to have a higher rate of diarrhea, though these findings have not been consistently reported in the literature. 16,17 Engraftment syndrome (ES) is a common complication of autologous HCT, typically developing within four days of granulocyte recovery. 19 ES may be classified by fever, skin rash, diarrhea, capillary leak syndrome, pulmonary infiltration, and hypoxia, among other symptoms.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[16][17][18] One study found PG melphalan to have a higher rate of mucositis and a separate study found PG-free melphalan to have a higher rate of diarrhea, though these findings have not been consistently reported in the literature. 16,17 Engraftment syndrome (ES) is a common complication of autologous HCT, typically developing within four days of granulocyte recovery. 19 ES may be classified by fever, skin rash, diarrhea, capillary leak syndrome, pulmonary infiltration, and hypoxia, among other symptoms.…”
Section: Introductionmentioning
confidence: 97%
“…14,15 While it was originally thought that PG-free melphalan may exhibit less adverse effects, comparative studies have found similar adverse effect profiles for both formulations. 1618 One study found PG melphalan to have a higher rate of mucositis and a separate study found PG-free melphalan to have a higher rate of diarrhea, though these findings have not been consistently reported in the literature. 16,17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different molecules that have been studied in the context of their potential anti-tumor effects, polyphenols and nitrogen mustards have shown to be effective against various types of tumor cell lines, such as lung, multiple myeloma, ovarian, breast and gastric cancer, among others [ 18 , 19 , 20 , 21 ]. Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is a naturally occurring polyphenol phytoconstituent obtained from Curcuma longa .…”
Section: Introductionmentioning
confidence: 99%